2009
DOI: 10.1029/2009ja014054
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and fragmentation properties of the micrometeoroid flux observed at Arecibo

Abstract: The micrometeor observations performed using the 430 MHz Arecibo Observatory radar have proven to be crucial for the understanding of meteoric effects on the aeronomy of the upper atmosphere. Meteors observed during the February 2001, 2006, and 2007 campaigns have been analyzed with a fast Fourier transform periodic search algorithm that automatically and uniformly detects meteor events between altitudes of 80 and 142 km. We present a description of the new technique used to detect meteors as well as the meteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…One advantage of this method is a reduction in processing time because the FFT only needs to be computed for the output of the algorithm, a much reduced amount of data. In addition, several other sophisticated and robust searching algorithms are described in the literature, including Mathews et al (2003) and Briczinski et al (2009).…”
Section: Observationsmentioning
confidence: 99%
“…One advantage of this method is a reduction in processing time because the FFT only needs to be computed for the output of the algorithm, a much reduced amount of data. In addition, several other sophisticated and robust searching algorithms are described in the literature, including Mathews et al (2003) and Briczinski et al (2009).…”
Section: Observationsmentioning
confidence: 99%
“…On the other hand, massive meteor trails have been observed by various radars (Briczinski et al, 2009;Ceplecha et al, 1998;Dyrud et al, 2011;Janches et al, 2001;Sugar et al, 2010;Zeng and Yi, 2011;Zhou and Perillat, 1998). Furthermore, there is some experimental evidence for a correlation between Na s and Es layer occurrence and meteor rates (Batista et al, 1989;Dou et al, 2010;Hansen and von Zahn, 1990;Hoeffner and Friedman, 2005;Höffner and Friedman, 2004), combined with the similar quasi-periodic oscillation and spatially localized scattering regions in Na s , Es and meteor trails, so that a possible role of meteor deposition in the formation of Na s layers should not be discarded.…”
Section: The Quasi-periodic Oscillation Phenomenon In Na S Layersmentioning
confidence: 99%
“…In this respect it should be noted that the metallic atoms detected were potassium and calcium, and these two metallic atoms have far lower abundances than those of sodium and iron in the meteor ablation region. Alternatively, the duration of these trails might be too short, on the order of milliseconds, to be detected by a lidar with a relative low repetition rate (Briczinski et al, 2009;Dyrud et al, 2011;Pfrommer et al, 2009). Only those metallic atomic trails strong enough and lasting long enough relative to the lidar would be discerned easily.…”
Section: The Quasi-periodic Oscillation Phenomenon In Na S Layersmentioning
confidence: 99%
“…Kero et al (2008) report three types of light curves-a smooth light curve event which simply outlines the antenna beam pattern and a ''beat pattern'' light curve event, shown to be consistent with two slowly separating particles, while yet more complex third type, found to be consistent with three or more fragments and/or continuous fragmentation. Briczinski et al (2009) and Sugar et al (2010) discuss the radar meteor head echo ''terminal events'' that are substantial through the meteor lifetime and then suddenly disappears below the noise level. Mathews et al (2010) reported many previously unaccounted features in the radar meteor return that are consistent with meteoroid fragmentation including ''terminal flare'' events.…”
Section: Introductionmentioning
confidence: 99%